East Africa's Infrastructure : A Regional Perspective - Ranganathan, Rupa; Foster, Vivien (2012)
Sound infrastructure is critical for growth in East Africa. During 1995-2005, improvements in infrastructure boosted growth by one percentage point per year, due largely to wider access to information and communication technologies (ICTs). Although power infrastructure sapped growth in other regions of Africa, it contributed 0.2 percentage points per year growth in East Africa. If East Africa's infrastructure could be improved to the level of the strongest performing country in Africa (Mauritius), regional growth performance would be boosted by some six percentage points, with power making the strongest contribution. East Africa's infrastructure ranks behind that of southern and western Africa across a range of indicators, though in terms of access to improved sources of water and sanitation and Internet density, it is comparable with or superior to the subcontinent s leader, southern Africa. By contrast, density of fixed-line telephones, power generation capacity, and access to electricity remain extremely low, though utility performance is improving through regional power trades. The road network is relatively good, although with some lengths of poor-quality or unpaved roads. Surface transport is challenged by border crossings, port delays, slow travel, limited railways, and trade logistics, but the region has a relatively mature and competitive trucking industry. Air transport benefits from a strong hub-and-spoke structure but has made little progress toward market liberalization. Of the seven countries in the region, four are landlocked, two have populations of fewer than 10 million people, and two have an annual gross domestic product of less than $10 billion. The difficult economic geography of East Africa makes a regional approach to infrastructure development necessary to achieve further improvement.